Influence of Microstructural Effect on Microvickers Hardness Properties of SiO2-Na2O-CaO (SNC) Waste Based Glass-ceramic - Nur Fadilah Baharuddin Pallan; N F Adnin; K A Matori; Mansor Hashim; F M Idris; I R Ibrahim; S N A Rusly; M Z A Khiri; Rodziah Nazlan; N Hapishah Abdullah; M S E Shafie; R S Aziz; et al. (IOP Publishing Ltd, 2024)
Volume : 1083